Efektifitas Permainan Bakiak Dalam Mengembangkan Keterampilan Pro-Sosial Anak Di Taman Kanak-Kanak Negeri Pembina 01 Sutera Kabupaten Pesisir Selatan - Sopia, Sopia; Marlina, Serli (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The background of this research is because there are children who when carrying out an activity at school prefer friends, lack a sense of concern for children, do not cooperate and are less responsible for the tasks carried out. This research approach is quantitative with a type of quasi-experimental (experimental quiz). The population in this study was the study group at Pembina State Kindergarten 01 Sutera which consisted of 3 classes, namely B1 17, B2 17 and B3 21. The samples in this study were group B1 and group B2 which were taken by purposive sampling technique, where the group B1 is used as the control class and B2 is used as the experimental class. The instrument in the research uses a test. The data analysis test used in this study was to compare the differences of the two average scores, so a t-test was performed. but before that, first do the normality test and homogeneity test. The results of this study show that: a) the homogeneity test is known to have a significant value (sig) 0.399> 0.05. It was concluded that the variance of the N-gain data for the experimental class and the control class was homogeneous: b) The sig(2-tailed) value was 0.001 based on table t 0.001<0.05. Thus it can be concluded that playing bakiak is more effective for stimulating children's prosocial skills in Pembina 01 Sutera Kindergarten. It can be concluded that clogs play is proven to be more effective on children's prosocial skills